Transportation systems security - McDougall, Allan (CRC Press, 2008)
Highlighting the importance of transportation to a country's infrastructure and survival, Transportation Systems Security presents the strategic and practical considerations involved in the implementation of physical, procedural, and managerial safeguards required to keep all modes of transportation up and running during an actual or potential disaster. Structured in an easy cognitive fashion, the book begins with a basic introduction providing terms and definitions. It describes both physical and information system layouts and defines who controls what parts of the process, how fa.